Routledge handbook of comparative political institutions - Gandhi, Jennifer; Ruiz Rufino, Rubén (Routledge, 2015)
"The Routledge Handbook of Comparative Political Institutions (HCPI) is designed to serve as a comprehensive reference guide to our accumulated knowledge and the cutting edge of scholarship about political institutions in the comparative context. It differs from existing handbooks in that it focuses squarely on institutions but also discusses how they intersect with the study of mass behaviour and explain important outcomes, drawing on the perspective of comparative politics"--
Keywords: Erde; Aufsatzsammlung; Vergleichende politische Wissenschaft; Politische Institution